Fruit quality parameters of some southern highbush blueberries (vaccinium xcorymbosum L.) grown in Andalusia (Spain) - Molina, J.M.=700 1 Calvo, D.; Medina, J.J.; Barrau, C.C.; Romero, F.
(En, Es)
Ilus., 17ref.
Keywords: ARANDANO AMERICANO; PROPIEDADES ORGANOLEPTICAS; CALIDAD; FRUTAS; METODOS ESTADISTICOS; ESPAÑA; VACCINIUM XCORYMBOSUM; SPANISH JOURNAL OF AGRICULTURAL RESEARCH